Dynamic characteristics of the annular rotor components in a rotor-bearing system under high frequency stress conditions. (March 2019) - Wang, Chenglin; Chen, Huating; Sun, Weichen; Wang, H J
Abstract: The dynamic characteristics of rotor components can directly affect the stability of a rotor-bearing system. Under certain conditions, such as high frequency stress, the dynamic performance of the rotor components is of particular importance. In this paper, a typical annular rotor is studied, and a testing system presented based on the base excitation resonance mass (BERM) method in order to measure key parameters, such as the radial and axial stiffness coefficients, damping coefficient, and loss factor. Based on this system, the dynamic characteristics of typical rotor components under radial and axial sine excitations below 2000 Hz were tested and analyzed. A predictive model of the characteristic parameters was then built based on the grey prediction method, and coupling between the radial and axial dimensions was evaluated. Further, the coupling mechanisms and relationships were analyzed, and the mechanism of interaction between microstructure features under high frequency stress was determined and combined with the changes to the internal microstructure of the rotor components to build a complete picture. Based on the experimental testing and theoretical results, our work suggests a strong correlation between the rotor stiffness coefficient and frequency of use, and thus provides empirical evidence and a reference for the future optimization of the dynamic characteristics of rotor components, in particular for the design of parameters for rotor components the experience high frequency stress conditions on the bearings.